Fidelização de clientes a partir do marketing de relacionamento no segmento de farmácias e drogarias - Pereira, Paula Fernanda Prado (2009)
The main purpose of the present essay is to verify to what extent the Relationship Marketing strategies may contribute to the increase in fidelity rates among customers in the drugstore/pharmacy chains in the city of São Paulo, Brazil, always searching for solutions to the issues arising from the vast competition in the segment today. The relevance of this theme is clear when one observes the difficulty found nowadays by organizations, in the most diverse market segments, in trying to make their trademarks able to conquer and retain customers, and gaining the customer fidelity. The research was of the exploratory kind, and the quantity methodological approach was conducted through a survey. This one was created from a question form with closed questions which enabled pre-determined answers and, aiming a certain degree of flexibility, some questions were half-open, making it possible for the interviewed to give an individual and specific answer. The sample was of the non-probability kind and counted on the participation of 232 individuals, who came to compose 108 valid question forms, according to three filter criteria adopted. Individuals belonging to classes A1, A2, B1 and B2 were chosen (even though they represent only 29% of the total Brazilian population), because it is believed that the Relationship Programs focus their efforts in people belonging to those classes. The application strategy adopted was the sending of the form through the Internet, using the website http://www.surveymonkey.com. A link for the research was sent to the email of the responding people, along with an invitation for taking part. Based on this research, it was possible to conclude that the process of client fidelity search in the segment of pharmacy and drugstores still remains in need of a deeper analysis, given that it was made clear that the Relationship Marketing was not the only and main requirement for client fidelity in that segment